Narrative Deserts and Embodied Meanings in the City : The Microstories of Ghent’s City Pavilion - Pint, Kris (Writingplace, 2022)
In his famous analysis of everyday life, Michel de Certeau examines how the technocratic discourse of production and consumption deprives urban inhabitants of meaningful stories. At the same time, he discerns a proliferation of microstories that resist this homogenization. We want to argue that de Certeau’s work is still very relevant for a discussion about meaningfulness and the contemporary city, if we take into account that these stories can also be antagonistic and even destructive. Following the work of Mark Johnson, we also would like to regard meaning as something that is not only linguistic, but emerges from an affective, sensorial interaction with our built environment. As a case study, we will discuss Ghent’s City Pavilion, designed by Robbrecht & Daem and Marie-José Van Hee architects, as a generator of stories and embodied meanings, both positive and negative.